Green, fair, and prosperous : paths to a sustainable Iowa - Connerly, Charles E., 1946- (Bur oak book., 2020)
"Iowa-and the larger Tallgrass Prairie region of which it is a part-are at a crossroads. Both must find more sustainable ways to develop or their environmental, economic, and social climates will continue to degrade. Iowa's economy is based heavily on agriculture, mainly corn, soybeans, hogs, cattle, and eggs. Agriculture comprises 25 percent of the state's economy, a percentage that is exceeded in the region only by South Dakota's 31 percent. Unfortunately, this economic model has a huge negative impact on the quality of Iowa's rivers and streams as well as the Mississippi and Missouri River basin and the Gulf of Mexico. Meanwhile, the state's population is increasingly diverse, including many new African-American and Hispanic residents, some of the latter undocumented. These populations are moving to Iowa to seek the economic opportunities offered by its relatively strong economy and respected education system. Yet African-Americans in Iowa face the highest black to white incarceration rate (13.16 to 1) in the United States. Although Hispanics are jailed at lower rates than African-Americans, they are still arrested at more than twice the rate of whites. Moreover, many Hispanics are drawn to Iowa by low-paying, dangerous jobs in meatpacking, and the possibility of deportation hangs over those without legal residency status. For development to be sustainable, society must balance economic development, environmental protection, and social justice. The purpose of this book is to make recommendations for how Iowans can achieve this balance"--